Suplementasi Vitamin D pada Wanita dengan Polycystic Ovarian Syndrome (PCOS) - Dian octaviana Aziza; Karin Indah Kurniati (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Polycyctic Ovarian Syndrome (PCOS) is the most common cause of anovulation and anovulation infertility. PCOS can be said to be endocrinopathy that often occurs in women of childbearing age and is associated with metabolic disorders and reproductive dysfunction. If no therapeutic management is performed in women with PCOS, complications can occur. Several pilot studies assess the therapeutic efficacy of vitamin D in metabolic parameters related to PCOS. Vitamin D is an essential steroid hormone that plays a role in maintaining calcium and phosphate hemostasis. Serum vitamin D concentrations are stated to be deficient if the 25 (OH) D level is 21-29 ng / mL and vitamin D deficiency is stated if the 25(OH)D level is <20 ng / mL.The effect of vitamin D deficiency are menstrual and fertility disfunction and also negative effect in cardiovascular system. Vitamin D has a direct effect on the process of folliculogenesis and oocyte maturation. Steroidogenesis in the ovaries that produce progesterone, estradiol and estron assisted calcitriol (vitamin D). Supplementation of vitamin D shows an increase in the action of granulosa cells ie progesterone secretion increases.